Ongoing monitoring of the performance of the internal audit activity in the public and private sectors - Bednarek, Piotr (Research Papers of Wrocław University of Economics, 2018)
The purpose of this article is to present how internal auditors in the public and private sectors define ongoing monitoring of internal audit activities. The empirical material for analysis was gathered from interviews conducted in Poland with 28 internal auditors employed in 30 organisations. The gathered data revealed many similarities and differences between internal auditors’ perception of the essence of this term. The results show that ongoing monitoring of internal audit activities is most often understood as supervising internal auditor by the CAE to ensure that an audit engagement is performed in accordance with the International Standards for Professional Practice of Internal Auditing, the objectives of the engagement are reached, and the work program is realized
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 125-135
Keywords: monitoring; control; quality; internal audit; improvement; monitorowanie; kontrola; jakość; audyt wewnętrzny; doskonalenie